Potential Prey Resources for Eagles in Lowland Shrubland Forest Ecosystems of Sulawesi, Indonesia - Wardiman Masud; Putu Supadma Putra; Chairil A; Ahmad Rifki Makkasau; Dian Ayu Lestari Hasannudin; iswanto iswanto (Politeknik Pertanian Negeri Samarinda, 2026)
Hasanuddin University Educational Forest is a habitat for eagles on the island of Sulawesi, with shrubland areas spanning 86.01 hectares utilized by these birds as their roaming territory. This study aims to identify potential prey for eagles within the shrubland areas of the Hasanuddin University Educational Forest. The research was conducted over a two-month period, from August to September 2024. Data were analyzed using both quantitative and descriptive approaches. Quantitative analysis was employed to calculate population density, species occurrence frequency, ecological indices of prey species, and the activity of prey species at the time of discovery. Descriptive analysis was utilized to interpret the vegetation conditions in the observation area. The study was conducted at three shrubland points dominated by the species Chromolaena odorata, Lantana camara, Leea indica, Melastoma malabathricum, and Stachytarpheta jamaicensis. Eleven potential prey species for eagles were identified, categorized into three groups: birds (45%), reptiles (45%), and mammals (10%). Coturnix ypsilophora (bird group) and Eutropis multifasciata (reptile group) exhibited the highest population densities and occurrence frequencies among the prey species. Rattus sp. was the sole prey species identified from the mammal group. Ecological index analysis indicated that the diversity, richness, and evenness of eagle prey types in the shrubland area were moderate. The dominant activities of prey species when observed were perching (bird group) and traversing (reptile group). The findings of this study suggest that the primary potential prey species for eagles in the shrubland area are Coturnix ypsilophora, Eutropis multifasciata, and Rattus sp.